Critical success factors (CSFS) of the pre-adoption and pre-implementation plan of Customer Relationship Management (CRM) system - Mohd, Haslina; Rababah, Khalid; Ibrahim, Huda (2011)
The success of Customer Relationship management (CRM) is not an easy thing to be achieved.The understanding of the main factors that could contribute in the success of CRM initiatives will make the difference toward successful CRM systems adoption and implementation.An extensive review of the literature was conducted in order to highlight the main success factors that if the organization be aware of and dealt with properly will achieve success and will gain the intended benefits of their CRM initiative or program.This paper revealed that top management support, managing organizational and cultural change, CRM understanding, organizational readiness, and users’ involvement are among the most important CRM systems success factors.In addition, this paper proposed plan of six success factors to be as a pre-adoption and pre-implementation plan for the successful adoption and implementation of CRM systems.